Oxidative Status and Lipid Metabolism Analytes in Dogs with Mast Cell Tumors: A Preliminary Study - Argyrios Ginoudis; Dimitra Pardali; Mathios E. Mylonakis; Androniki Tamvakis; Asta Tvarijonaviciute; Evgenia Lymperaki; Jose Joaquin Ceron; Zoe Polizopoulou (Antioxidants)
Mast cell tumors (MCTs) are common skin neoplasms in dogs. Prognostic indicators include histologic grade, clinical stage, high Ki-67 index, elevated argyrophilic nucleolus organizer regions (AgNOR) index, c-kit mutations, and recurrence after surgery. Blood serum redox status has been shown to correlate with prognostic factors in canine lymphoma and mammary tumors. This study aimed to assess the correlation between established prognostic factors and serum redox status and lipid metabolism analytes in dogs with MCTs. Dogs with cutaneous (n = 33) or subcutaneous (n = 6) MCTs, without comorbidities, were studied. Staging was evaluated based on cytology of regional lymph nodes and ultrasound-guided liver and spleen aspiration cytology. Histologic grading and immunohistochemical staining for Ki-67 and KIT patterns were performed on excised tumor specimens. Dogs were categorized by Patnaik grading (1–3), Kiupel grading (low/high), metastatic status, Ki-67 positive nuclei per cm2 (>23 or ≤23), and KIT pattern (I, II–III). Paraoxonase-1, Butyrylcholinesterase, Cupric Reducing Antioxidant Capacity (CUPRAC), Diacron Reactive Oxygen Metabolites (d-ROMs), and oxy-adsorbent levels were measured before any therapeutic intervention. ANOVA and independent t-tests were used to detect differences in the mean values among groups. Paraoxonase-1 activity was significantly lower in Patnaik grade 3 (p = 0.003) and Kiupel high-grade (p = 0.022) MCTs. No significant differences were found in CUPRAC, d-ROMs, or oxy-adsorbent levels across different prognostic groups. This study found a significant correlation between histologic grading and Paraoxonase-1 activity, suggesting a potential role of Paraoxonase-1 as a prognostic biomarker in canine MCTs.